VD_FINDINFO PPD 12/10 - 47/2011 vom 18. Juli 2011 - VD Tribunal cantonal (2011)
CONVENTION DE PARTAGE, DROIT INTERNATIONAL PRIVÉ, DÉCLARATION D'EXÉCUTION, PRÉVOYANCE PROFESSIONNELLE | 142 al. 2 CC, 73 al. 3 LPP, 111 al. 1 LPA-VD